Activity-dependent modulation of inhibitory synaptic kinetics in the cochlear nucleus - Nerlich, Jana; Keine, Christian; Rübsamen, Rudolf; Burger, R. Michael; Milenkovic, Ivan (Frontiers in Neural Circuits, 2014)
Spherical bushy cells (SBCs) in the anteroventral cochlear nucleus respond to acoustic stimulation with discharges that precisely encode the phase of low-frequency sound. The accuracy of spiking is crucial for sound localization and speech perception. Compared to the auditory nerve input, temporal precision of SBC spiking is improved through the engagement of acoustically evoked inhibition. Recently, the inhibition was shown to be less precise than previously understood. It shifts from predominantly glycinergic to synergistic GABA/glycine transmission in an activity-dependent manner. Concurrently, the inhibition attains a tonic character through temporal summation. The present study provides a comprehensive understanding of the mechanisms underlying this slow inhibitory input. We performed whole-cell voltage clamp recordings on SBCs from juvenile Mongolian gerbils and recorded evoked inhibitory postsynaptic currents (IPSCs) at physiological rates. The data reveal activity-dependent IPSC kinetics, i.e. the decay is slowed with increased input rates or recruitment. Lowering the release probability yielded faster decay kinetics of the single- and short train-IPSCs at 100Hz, suggesting that transmitter quantity plays an important role in controlling the decay. Slow transmitter clearance from the synaptic cleft caused prolonged receptor binding and, in the case of glycine, spillover to nearby synapses. The GABAergic component prolonged the decay by contributing to the asynchronous vesicle release depending on the input rate. Hence, the different factors controlling the amount of transmitters in the synapse jointly slow the inhibition during physiologically relevant activity. Taken together, the slow time course is predominantly determined by the receptor kinetics and transmitter clearance during short stimuli, whereas long duration or high frequency stimulation additionally engage asynchronous release to prolong IPSCs.